2010 7th International Conference on the European Energy Market 2010
DOI: 10.1109/eem.2010.5558732
|View full text |Cite
|
Sign up to set email alerts
|

Integration of renewable energy in the European power grid: Market mechanism for congestion management

Abstract: With the increased use of wind energy several Transmission System Operators (TSO) have increasing difficulties for congestion forecasting due to the unpredictable nature of the energy source. To maintain the state of the system within acceptable and secure operating conditions, the TSOs require the curtailment of the production of generators to avoid local congestion on the power grid. These actions reduce the revenue of renewable producers and limit the development of green energy. This is because renewable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…From the perspective of long-term planning, the congestion management problem is affected by variations in the power flow pattern [1][2][3][4][5][6]. On the other hand, regarding the shortterm operation, increasing uncertainty related to REPPs affects the congestion management problem [7][8][9][10][11]. In [4,5], a method for managing network congestion based on the market mechanism is introduced to increase the share of REPPs in the electrical power generation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of long-term planning, the congestion management problem is affected by variations in the power flow pattern [1][2][3][4][5][6]. On the other hand, regarding the shortterm operation, increasing uncertainty related to REPPs affects the congestion management problem [7][8][9][10][11]. In [4,5], a method for managing network congestion based on the market mechanism is introduced to increase the share of REPPs in the electrical power generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another way to increase the share of REPPs is re‐dispatching power plants during congestion while improving network reliability. It must be performed by a supervisor who considers REPPs and GenCos simultaneously [8, 9, 12]. Similarly, [13] presents a new method for rescheduling to improve the impact of wind farms integration on congestion management.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of wind and solar resources creates new challenges in energy regulation: curtailment and the setting up of additional storage capacity are traditional answers to the need of making the increasing RES share available, even if with many shortcomings and economic losses [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…At 80%, the number of overloading cases has been increased with a total of 192 for test 1 and 32 for test 2. It is in light of this point that line [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] was the first to be chosen to implement the DLR. This line has a base case ampacity of 0.5 kA with a resistance of 0.11 Ω/km.…”
Section: Determining Suitable Dlr Candidatesmentioning
confidence: 99%
“…In number of studies transmission congestion has been identified as the major curtailing factor for wind power generation [6][7] and requires considerable time and investment to develop a new transmission network. The convection cooling of the conductors will be at its highest during times of high wind generation assuming high wind speeds experienced at transmission lines, hence wind cooling effect can be effectively utilised without implementing expensive transmission network upgrade.…”
Section: Introductionmentioning
confidence: 99%